Sporadic multiple parathyroid gland disease—a consensus report of the European Society of Endocrine Surgeons (ESES) - Barczyński, Marcin (Langenbecks Arch Surg, 2015)
BACKGROUND: Sporadic multiglandular disease (MGD) has been reported in literature in 8–33 % of patients with primary hyperparathyroidism (pHPT). This paper aimed to review controversies in the pathogenesis and management of sporadic MGD. METHODS: A literature search and review was made to evaluate the level of evidence concerning diagnosis and management of sporadic MGD according to criteria proposed by Sackett, with recommendation grading by Heinrich et al. and Grading of Recommendations, Assessment, Development and Evaluation (GRADE) system. Results were discussed at the 6th Workshop of the European Society of Endocrine Surgeons entitled ‘Hyperparathyroidism due to multiple gland disease: An evidence-based perspective’. RESULTS: Literature reports no prospective randomised studies; thus, a relatively low level of evidence was achieved. Appropriate surgical therapy of sporadic MGD should consist of a bilateral approach in most patients. Unilateral neck exploration guided by preoperative imaging should be reserved for selected patients, performed by an experienced endocrine surgeon and monitored by intraoperative parathormone assay (levels of evidence III–V, grade C recommendation). There is conflicting or equally weighted levels IV–V evidence supporting that cure rates can be similar or worse for sporadic MGD than for single adenomas (no recommendation). Best outcomes can be expected if surgery is performed by an experienced parathyroid surgeon working in a high-volume centre (grade C recommendation). Levels IV–V evidence supports that recurrent/persistence pHPT occurs more frequently in patients with double adenomas hence in situations where a double adenoma has been identified, the surgeon should have a high index of suspicion during surgery and postoperatively for the possibility of a four-gland disease (grade C recommendation). CONCLUSIONS: Identifying preoperatively patients at risk for MGD remains challenging, intraoperative decisions are important for achieving acceptable cure rates and long-term follow-up is mandatory in such patients.